Connecting epigenetics and inflammation in vascular senescence: state of the art, biomarkers and senotherapeutics - Fraile-Martinez, Oscar; De Leon-Oliva, Diego; Boaru, Diego Liviu; De Castro-Martinez, Patricia; Garcia-Montero, Cielo; Barrena-Blázquez, Silvestra; García-García, Joaquin; García-Honduvilla, Natalio; Alvarez-Mon, Melchor; Lopez-Gonzalez, Laura; Diaz-Pedrero, Raul; Guijarro, Luis G.; et al. (Frontiers in Genetics, 2024)
Vascular diseases pose major health challenges, and understanding their underlying molecular mechanisms is essential to advance therapeutic interventions. Cellular senescence, a hallmark of aging, is a cellular state characterized by cell-cycle arrest, a senescence-associated secretory phenotype (SASP), macromolecular damage, and metabolic dysregulation. Vascular senescence has been demonstrated to play a key role in different vascular diseases, such as atherosclerosis, peripheral arterial disease, hypertension, stroke, diabetes, chronic venous disease, and venous ulcers. Even though cellular senescence was first described in 1961, significant gaps persist in comprehending the epigenetic mechanisms driving vascular senescence and its subsequent inflammatory response. Through a comprehensive analysis, we aim to elucidate these knowledge gaps by exploring the network of epigenetic alterations that contribute to vascular senescence.In addition, we describe the consequent inflammatory cascades triggered by these epigenetic modifications. Finally, we explore translational applications involving biomarkers of vascular senescence and the emerging field of senotherapy targeting this biological process.